On Orders of Approximation Functions of Generalized Mixed Smoothness in Lorentz Spaces - Akishev, Gabdolla (Sarajevo Journal of Mathematics, 2022)
We consider the Lorentz space with mixed norm of periodic functions of many variables and Nikol’skii-Besov type classes of the generalized mixed smoothness. We have obtained estimates of the best approximation by trigonometric polynomials with the harmonics from the hyperbolic crosses of functions fromNikol’skii-Besov’s type classes of the generalized mixed smoothness in the Lorentz space with the mixed norm.